LONG-LASTING CONTROL OF HER-2 POSITIVE DISSEMINATED BREAST CANCER IN A REPRODUCTIVE AGED PATIENT - A. V. Vazhenin; N. V. Voroshina; O. S. Tereshin; N. S. Dubrovskaya (Сибирский онкологический журнал)
Background. Breast cancer ranks as the second most common cancer (14.9 %) and the most common female cancer (20.9 %) in Russia. at the time of diagnosis, 11.0 % of patients have already developed metastases, and 10.3 % of patients die within the first year of diagnosis from disease progression. distant metastasis is the leading cause of death from breast cancer, and brain metastasis is a significant prognostic factor for poor survival.Case description. We report the case of a long-lasting control of advanced breast cancer with brain metastases in a 32-year-old woman. low grade tubular breast carcinoma was histologically confirmed. immunohistochemical study: eR-ts-4 points, PR-ts – 3 points, Her-2 positive, Ki67 – 35.0 %. BRCa1 5382ins C mutation was not detected. the long-term use of therapy with lapatinib and capecitabine was described.Conclusion. this case demonstrates the feasibility of long-term (31 months) control over Her-2 positive disseminated breast cancer with multiple metastases to the brain and bones, while maintaining the quality of life and social activity of a young patient. despite the risks associated with whole brain radiotherapy, no cognitive impairment was observed. therapy with lapatinib and capecitabine was effective for 28 months with good tolerance.